PERWALIAN DAN ISU-ISU KONTEMPORER - Khair, Uslyfatul (MADDIKA : Journal of Islamic Family Law, 2023)
This article reviews trusts. Guardianship is one of the important problems among the people of Indonesia which relies on the law that regulates the relationship between individuals called civil law, by looking at the growth of cases of the discovery of babies who do not have parents, of course the laws related to and regulating these matters must be neatly arranged to be able to solve these things, even though in the State of Indonesia there are already rules that regulate this, However, the author feels that it is still necessary to conduct legal research by comparing the new rules with the old rules, so that the author can find out whether the current rules have added value from the previous rules or vice versa.